Jogando meu corpo no mundo: relações entre "conflito urbano" e "acumulação social da diferença" - Cunha, Janaina Maldonado Guerra da (2020)
This dissertation aims to understand the relationship between urban conflict and difference in the contemporary São Paulo. Based on the ethnographic study conducted in a periphery of the East Zone of São Paulo, I discuss the grammars and normative regimes that emerge from the differentiation processes in operation in cities. I start from the idea that the categories that mark the difference guide the constitution of the grammars mobilized by the subjects for the understanding of social problems, in each daily situation. I consider that the meanings of these categories are disputed through social relations, and are related to the production of orders and formations of sovereignty in urban spaces. Theoretically, I propose a dialogue between two distinct fields of study: Urban Sociology and Studies of Difference. From this, I suggest that the urban conflict is crossed by a process of ‘social accumulation of difference’ from which more or less reified subject positions emerge.